Work organization in dynamics of innovation: Evidence in Public Administration - Cristina Camila Teles Saldanha; Marcus Vinicius Gonçalves da Cruz (Cadernos Gestão Pública e Cidadania)
The article aims to analyze the perceptions of civil servants regarding the structuring factors of work organization for innovation in the public sector. Theoretical support indicates that work organization practices are linked to the aspects underlying the innovations. Although there is an expectation for greater autonomy and flexibility that contribute to innovations, the formalization of work persists in public organizations. Qualitative and descriptive research was carried out, through the study of multiple cases in sectors that work directly with innovations and in people management units, responsible for rethinking ways of structuring work at federal and state levels. Work organization was broken down into structuring factors, selected after literature review, documental survey, and content analysis. The perceptions of these factors were captured in semi-structured interviews with open-ended and close-ended questions, the latter linked to the numerical representations of these factors for 14 interviewees. The findings indicated that factors such as interdisciplinary teams and networks reflected as good practices for innovation, while autonomy, flexibility and telework are emerging. The organizational mobility factor faces legal and managerial restrictions. It was also found that the lack of resources encourages the search for viable and creative alternatives. This research contributes theoretically to portray structuring factors of work organization linked to strategic people management actions as incentives to innovations in the public sector. Empirically it reveals the adjustments in the organization of work aimed at innovation as adaptation to the context. Work organization becomes an imperative demand in the dynamics of innovation in public administration.